Application of a Robin boundary condition to surface waves - Christensen, Kai Håkon; Weber, Jan Erik Hobæk (Frontiers in Marine Science, 2023)
Surface effects on deep-water gravity waves are investigated theoretically by the application of a Robin boundary condition with a complex Robin parameter, R=R_r+iR_i. The Robin condition combines the shear stress and the horizontal velocity at the ocean surface. We show that this condition describes wave damping related to surface phenomena like elastic films or thin viscous fluid layers. It also may model wave generation by oscillating surface stresses depending on the signs and magnitudes of R_r and R_i.